SOCIAL DETACHMENT AND FALSE CONSCIOUSNESS IN THE LOTTERY IN BABYLON BY JORGE LUIS BORGES - Cantika, Rita Apriliya; Wardani, Tia Ivanka; Asy-Syaffa, Alifya Rahma; Hariyanto, Alifia Kamila Jasmine Putri; Fiorella, Sonya Ivanda; Saraswati, Rina (Jurusan Sastra Indonesia, 2023)
This study analyzes the portrayal of social class between The Company that ran the lottery as the upper class and the citizens who were the lottery participants as the lower class in The Lottery in Babylon by Jorge Luis Borges. This study used the theory from Karl Marx regarding the existence of the false consciousness of the bourgeoisie toward the proletariats. The qualitative approach was employed in this study to collect the essence of the short story. It is found that according to Marxist theory, The Lottery of Babylon portrays the existence alienation from the existence of the Lottery in which defines one's social class and fate.